Effect of starter culture sourdough prepared with Lactobacilli and Saccharomyces cerevisiae on the quality of hull-less barley-wheat bread - Cakir, Elif; Arici, Muhammet; Durak, Muhammed Zeki (ELSEVIER, 2021)
The aim of the present study was to investigate the microbial and technological characterization of barley-wheat flour (with 25%, 50%, 75% wheat flour added) breads made from hull-less barley sourdough that was prepared with a starter culture of Lb. plantarum SAB15, Lb. brevis SAB31 and S. cerevisiae SAM1-4. The yeasts isolated from spontaneous hull-less sourdough were sequenced with 26S rRNA gene via identification of the dominant species of S. cerevisiae with FTIR. Hull-less barley, with 13.6% protein, 1.47% ash, 66.15% water absorption and 21 ml sedimentation value, was added to wheat flour and protein, water absorption, and ash values decreased while sedimentation values increased. Hull-less barley-wheat bread samples containing starter culture was obtained with higher volume, specific volume and lower hardness than breads containing spontaneous culture. Especially breads with 25% and 50% barley mix were found to be the best ratios for hull-less barley bread. Although bread containing 75% and 100% barley flour scored low, those containing starter culture scored positively in terms of hardness and chewiness, and were accepted by consumers. With more barley added, there was higher a* and lower b* in the bread, while the breads with starter culture were found to be less yellow and red.
Keywords: Sourdough fermentation; Starter culture; Lactic acid bacteria; Yeast; Hull-less barley bread; LACTIC-ACID BACTERIA; PHYSICOCHEMICAL PROPERTIES; FLOUR; FERMENTATION; CEREAL; DOUGH; FOOD; BIODIVERSITY; PRODUCTS; Food Science & Technology